2020
DOI: 10.1002/glia.23776
|View full text |Cite
|
Sign up to set email alerts
|

The mechanistic target of rapamycin pathway downregulates bone morphogenetic protein signaling to promote oligodendrocyte differentiation

Abstract: Oligodendrocyte precursor cells (OPCs) differentiate and mature into oligodendrocytes, which produce myelin in the central nervous system. Prior studies have shown that the mechanistic target of rapamycin (mTOR) is necessary for proper myelination of the mouse spinal cord and that bone morphogenetic protein (BMP) signaling inhibits oligodendrocyte differentiation, in part by promoting expression of inhibitor of DNA binding 2 (Id2). Here we provide evidence that mTOR functions specifically in the transition fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 62 publications
(121 reference statements)
0
25
0
Order By: Relevance
“…Through both genetic and pharmacological manipulations of this pathway, it has become apparent that mTOR is a key signal transduction pathway for oligodendrocyte differentiation (Ryskalin et al, 2017; Tyler et al, 2009; Wood et al, 2013). Moreover, mTOR regulates oligodendrocyte differentiation during the transition from the late progenitor to the immature oligodendrocyte (Ornelas et al, 2020). Therefore, we hypothesized that LIF might be stimulating the mTOR pathway.…”
Section: Resultsmentioning
confidence: 99%
“…Through both genetic and pharmacological manipulations of this pathway, it has become apparent that mTOR is a key signal transduction pathway for oligodendrocyte differentiation (Ryskalin et al, 2017; Tyler et al, 2009; Wood et al, 2013). Moreover, mTOR regulates oligodendrocyte differentiation during the transition from the late progenitor to the immature oligodendrocyte (Ornelas et al, 2020). Therefore, we hypothesized that LIF might be stimulating the mTOR pathway.…”
Section: Resultsmentioning
confidence: 99%
“…Hypoxic conditions result in increased HIF1/2a ( Yuen et al, 2014 ). mTOR deletion leads to increased expression of the oligodendrocyte maturation inhibiting promotor ID2 ( Ornelas et al, 2020 ). Reduction of Tsc1/2 results in hyperactive mTOR, increased translation and ER stress, and increased Fas-JNK signaling ( Jiang et al, 2016 ).…”
Section: Intrinsic Mechanisms Regulating Premyelinating Oligodendrocyte Survival and Integrationmentioning
confidence: 99%
“…Our recently published study demonstrated that mTOR signaling normally downregulates the bone morphogenetic pathway to promote the transition from the early OPC to immature oligodendrocyte (Ornelas et al, 2020). To determine whether mTOR signaling is required for KIF1B maintenance following the initial transition of the early bipolar OPCs to late progenitor cells, we used a modified in vitro differentiation paradigm where we allowed OPCs to differentiate normally for 48 h prior to inhibiting mTOR with rapamycin (Tyler et al, 2009;Fig.…”
Section: Mtor Promotes Kif1b Expression In Oligodendrocytes In the Spmentioning
confidence: 99%